1976
DOI: 10.2307/1128460
|View full text |Cite
|
Sign up to set email alerts
|

Free-Play Fantasy Behavior in Preschool Children: Relations among Gender, Age, Season, and Location

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…First, in accordance with previous research (Johnson & Ershler, 1981;Rubin et al, 1978;Sanders & Harper, 1976) and the developmental course of pretend play described by El'Konin (1966) and Piaget (1962), older triads were expected to engage in significantly more cooperative pretend play than younger triads. First, in accordance with previous research (Johnson & Ershler, 1981;Rubin et al, 1978;Sanders & Harper, 1976) and the developmental course of pretend play described by El'Konin (1966) and Piaget (1962), older triads were expected to engage in significantly more cooperative pretend play than younger triads.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…First, in accordance with previous research (Johnson & Ershler, 1981;Rubin et al, 1978;Sanders & Harper, 1976) and the developmental course of pretend play described by El'Konin (1966) and Piaget (1962), older triads were expected to engage in significantly more cooperative pretend play than younger triads. First, in accordance with previous research (Johnson & Ershler, 1981;Rubin et al, 1978;Sanders & Harper, 1976) and the developmental course of pretend play described by El'Konin (1966) and Piaget (1962), older triads were expected to engage in significantly more cooperative pretend play than younger triads.…”
supporting
confidence: 81%
“…There is evidence that boys tend to be very mobile while engaging in pretend play, whereas girls are more likely to be sedentary (Pulaski, 1970;Sanders & Harper, 1976). There is evidence that boys tend to be very mobile while engaging in pretend play, whereas girls are more likely to be sedentary (Pulaski, 1970;Sanders & Harper, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…It is notable the investment that research has been dedicated to the construction and validation of reliable assessment measures of play. Regarding the country of origin of the studies included in this systematic review, it is possible to observe that the USA is the country with most studies (n = 34) (Barton, 2015;Bulotsky-Shearer et al, 2012;Coolahan et al, 2000;Coplan & Rubin, 1998;Coplan et al, 2001Coplan et al, , 2014Esposito & Koorland, 1989;Fantuzzo et al, 1995;Farmer-Dougan & Kaszuba, 1999;Farver & Lee-Shin, 2000;Fehr & Russ, 2013Gagnon et al, 2014;Gal-Szabo et al, 2019;Hart & Sheehan, 1986;Hartle, 1996;Johnson et al, 1980;Kinsman & Berk, 1979;LaForett & Mendez, 2017;Lagacé-Séguin & d'Entremont, 2006;Marcelo & Yates, 2020;Maxwell et al, 2008;Minnett et al, 1994;Nelson et al, 2017;Pierce-Jordan & Lifter, 2005;Pollack et al, 2016;Roopnarine et al, 1992;Sanders & Harper, 1976;Saracho, 1995Saracho, , 1996Saracho, , 1999Shire et al, 2018;Wilson, 2015;Wintre, 1989), contributing to the construction and validation of some assessment instruments of play (e.g., PPBS; PSPI; PIPPS; APS-P; APS-P-BR).…”
Section: Country Of Origin Of the Studiesmentioning
confidence: 99%
“…Hence, one also has to wonder about how the lack of girls in the class may have an impact on the boys. It must change the quality, type, and activity level of play within the classroom (Alexander & Hines;Hayden-McPeak et al, 1993;Sanders & Harper, 1976).…”
Section: Interviews With Pre-k Teachersmentioning
confidence: 99%
“…Maccoby also postulated that girls may be cautious of boys' active play styles which feature characteristics of dominance and competition, and perhaps even more importantly, girls have difficulty influencing the play scenario when boys are involved. Boys have been found to be more likely to engage in solitary outdoor fantasy play whereas girls engage in traditional roles of "house" and "school" (Sanders & Harper, 1976). Sanders and Harper also indicated that boys play outdoors more, and are encouraged to engage in active, large motor, physically challenging play.…”
Section: Impact On Playmentioning
confidence: 99%